(untitled) (Al-Aasar, 2025)
Wahi (the Qur’an) is the primary and most authoritative source of Islamic teachings, while the blessed life of its Hamil-e-Wahi, the Prophet Muhammad ﷺ, serves as the practical manifestation and interpretation of the divine message. The Qur’an represents the Word of Allah, and the Prophet ﷺ is the chosen Messenger who conveyed it to humanity; together, they form the foundation of Islamic faith and guidance. For more than two centuries, Orientalist scholarship has raised various objections concerning the authenticity, preservation, and divine origin of Wahi, alongside critical challenges directed toward the esteemed personality and Prophetic biography (Sirah) of the Prophet Muhammad ﷺ. Such critiques have often sought to undermine confidence in Islam’s primary sources and create skepticism regarding Muslim beliefs and historical tradition. In response, Muslim scholars have developed comprehensive intellectual rebuttals grounded in Islamic methodologies, sound epistemological principles, and rigorous academic research. This study critically analyzes the major Orientalist objections against the Qur’an and the Prophet ﷺ, examining their assumptions, methodological flaws, and underlying ideological biases. The findings reveal that many of these criticisms stem from preconceived notions, selective readings, and a lack of engagement with the Islamic scholarly tradition. Ultimately, the research highlights the strength and resilience of Islamic scholarship in defending the authenticity of Wahi and the honor of its Hamil-e-Wahi ﷺ.